2021
DOI: 10.21203/rs.3.rs-620829/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of an Autophagy-Related lncRNA Prognostic Signature and Related Tumor Immunity Research in Lung Adenocarcinoma

Abstract: Background: Autophagy is closely associated with the tumor immune microenvironment (TIME) and prognosis of patients with lung adenocarcinoma (LUAD). In the present study, we established a signature based on long noncoding RNAs (lncRNAs) related to autophagy (ARlncRNAs) to investigate the TIME and survival of LUAD patients.Methods: We selected ARlncRNAs associated with prognosis to construct a model, and divided each sample into different groups based on risk score. Subsequently, Kaplan-Meier survival analysis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In recent years, the emergence of bioinformatic analyses has functioned as an effective and reliable pattern to study the complex molecular pathogenesis of NSCLC 29 . Increasing scholars have screened effective and reliable targets through bioinformatics analyses to predict the prognosis, explore the tumor immunity, and even select suitable anti‐tumor drugs of patients with tumors, which benefited greatly the patients with malignant tumors 30,31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the emergence of bioinformatic analyses has functioned as an effective and reliable pattern to study the complex molecular pathogenesis of NSCLC 29 . Increasing scholars have screened effective and reliable targets through bioinformatics analyses to predict the prognosis, explore the tumor immunity, and even select suitable anti‐tumor drugs of patients with tumors, which benefited greatly the patients with malignant tumors 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…29 Increasing scholars have screened effective and reliable targets through bioinformatics analyses to predict the prognosis, explore the tumor immunity, and even select suitable anti-tumor drugs of patients with tumors, which benefited greatly the patients with malignant tumors. 30,31 CDCA5, acts as a cell cycle regulator, is combined with nuclear chromatin from S phase to metaphase and is subsequently released into the cytoplasm upon nuclear envelope breakdown. 9 Through bioinformatics analyses, we concluded that overexpression of CDCA5, an oncogene overexpressed in 18 common malignant tumors, was 19 It is worth mentioning that cyclin E is located downstream of the p53-p21 signaling pathway and regulates downstream cell cycle arrest (Figure 4).…”
Section: Silencing Cdca5 Leads To Apoptosis and G1 Phase Arrest Cell ...mentioning
confidence: 99%
“…In recent years, with the development of bioinformatic analyses, research has established reliable prognostic signatures based on mRNAs or lncRNAs to predict the prognosis of patients with various malignancies. 26,27 We were eager to build a new algorithm to predict the survival outcomes of patients with LUAD and provide valuable recommendations for the selection of appropriate anti-tumor drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The constructed prognostic signature was subjected to internal verification by dividing the patients with LUAD randomly into a training group and a testing group, which proved the reliability of the signature. Moreover, compared with the traditional prognostic signature that divided patients into 2 risk groups, [39] we divided the patients into 4 groups based on molecular subtypes and the prognostic signature, which could offer patients with LUAD more precise treatment. We included chemotherapy (Paclitaxel), targeted therapy (Erlotinib, Gefitinib), and immunotherapy (PD-1, PD-L1, CTLA-4, and HAVCR-2 therapy), which are currently recommended for patients with advanced lung cancer.…”
Section: Discussionmentioning
confidence: 99%